An industry update: the latest developments in therapeutic delivery. (February 2017) - Simpson, Iain
This Industry Update covers the period from 1 October through to 31 October 2016, and is based on information sourced from company press releases, scientific literature, patents and various news websites. The month saw several news items covering drug-delivery devices, including a new sensor to monitor and support the use of inhalers; launch in the UK of a new autoinjector for Cimzia ®, UCB's rheumatoid arthritis drug; and approval of Roche's Lucentis ® in a prefilled syringe. Research was also published to show the value of continuous blood pressure monitoring in dementia management. Astellas announced the acquisition of German pharmaceutical company Ganymed while Sunovion completed its purchase of Cynapsus. A new EU-funded collaboration was announced looking at the value of PET-based biomarkers in Alzheimer's disease. GSK gained USA approval for its shingles vaccine, but Novo Nordisk and Sanofi received complete response letters from the US FDA, requiring further information before regulatory review of their drug submissions can be completed. The UK's NICE concluded that a drug marketed by BMS to treat a common type of lung cancer was not cost–effective and Cornell University announced results showing that its nanoparticle technology, originally developed as a tumor biomarker, could be effective in directly treating the disease.